A study of improving thermal environment of external louver through establishment of test bed - Pil Kwon, Sun; Jun Jung, Jae; Jo Jung, Byoung (International Journal of Engineering and Technology, 2018)
Background/Objectives: To improve a thermal load by increasing internal thermal effect of a building from direct solar radiation through an increase of glass windows.Methods/Statistical analysis: Through the establishment of test beds of the same size, the data of temperature, humidity, solar insolation and PMV of each test bed with or without external louver are acquired to analyze thermal environmental with the simulation.Findings: For the analysis of thermal environment, the amount of energy consumption has been analyzed through the simulation and the data of temperature, humidity, solar insolation and PMV have been acquired for the analysis. With the simulation, about 20% energy saving has been confirmed and the daily averages of temperature and humidity between 8AM to 7PM have been calculated to calculate the maximum temperature difference to be 9.4â„ƒ. The solar insolation between 9AM and 7PM was 300W/m2 or below.Improvements/Applications: The improvement of thermal effect with an external louver has been confirmed. It may be applied to the louver system to improve building thermal environment, awning to control direct solar radiation, blind to improve uniformity of illumination intensity toward building during daytime, external blind and ceiling louver system.Â